DINAMIKA PENYELESAIAN SENGKETA LAUT TAKESHIMA ANTARA JEPANG DAN KOREA SELATAN BERDASARKAN TINJAUAN UNCLOS 1982 - Nababan, Grace Oktavia; Rahma, Zilva Aulia; Inisyaputra, Beben; Septaria, Ema; Adepio, M Ilham (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2025)
This study examines the maritime dispute between Japan and South Korea over Takeshima Island (Dokdo) using international maritime law, particularly UNCLOS 1982. It explores dispute resolution mechanisms such as conciliation (Article 282), arbitration (Annex VII), and the International Tribunal for the Law of the Sea (Article 287, Annex VI). The study uses normative legal research to analyze key UNCLOS principles, including peaceful dispute settlement (Article 279), consultation in good faith (Article 283), equitable maritime delimitation (Articles 74 and 83), and cooperation in managing exclusive economic zones and conserving marine resources (Articles 56 and 61). Japan promotes resolution through legal means, while South Korea maintains de facto control and rejects international adjudication. The dispute concerns both sovereignty and natural resource rights. The study concludes that UNCLOS 1982 provides a solid legal and normative framework for peaceful settlement, but its effectiveness depends on the political will of both countries to uphold international maritime law.